Research of the shimmering failures predicting method based on the emissions theory - Недоступ, Леонід Аврамович; Кіселичник, Мирослав Дмитрович; Заярнюк, Павло Михайлович (Eastern-European Journal of Enterprise Technologies, 2014)
Intermittent failures of REE (radio electronic equipment) are hard to predict, while they may lead to critical consequences. We propose the method, based on the theory of runs of random processes for predicting the parametric reliability of REE. This method allows predicting the duration of runs, their number and average duration of one run in the interval from 0 to T, on condition of the known three-dimensional random variable distribution law. The analytical and graphic dependencies for determining the parameters of the random process of change of REE defining parameter are given in the paper. The proposed method allows taking into account intermittent failures and predicting reliability for stationary and non-stationary processes. In addition, as a result of some simplifications, predicting is carried out with the known regression of expected value and variance, as well as the known random process distribution law. The main advantage of the developed method is that it allows predicting the reliability of radio electronic equipment both in the case of the stationary process, and in the cases of the process with periodic component and quasideterministic random process.